Decisions of Purchase and Consumption of Light Non-Alcoholic Beverages in the Metropolitan District of Quito - Pila-Tituaña, Alcívar (2017)
There’s a problem evidenced in the current increase in mortality due to non-communicable diseases caused by overweight and obesity, that lead the consumer to search for healthier way of life, with low calorie, fat and sugar free diet that has created a massive response from the food industry that offers to the market products specially designed to meet the expectations and specific health and wellness needs of the consumer. The present study aims to clarify how the decisions of purchase and consumption of non-alcoholic light drinks are related to the light lifestyle and the culture of feeling and looking good and how these decisions are manifested in consumers of the city of Quito. Among the results of the study it was possible to demonstrate that the main motivations that influence the purchase and consumption of non-alcoholic light drinks are health and physical and aesthetic wellbeing, although the consumer do not know about the true benefits or damages of these products. This study uses the survey as research technique and corresponds to a quantitative approach with a non-experimental design, transectional temporality and descriptive and correlational scope.